2007
DOI: 10.1300/j010v44n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Supports the Value of Social Work in Hospitals

Abstract: The value of hospital social work is supported by one hospital's tracking system that monitored social work discharge services and compared outcome with non-social work discharges. The sample consisted of a total of 64,722 patients admitted to the "med-surg" hospital unit over a two and one-half year time period from 2002 to 2004. Of the total patients in the sample, 15.7% (n = 10,156) had social work involvement. Sixty percent of the social worker patients were age 70 or over compared with the mean age of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 18 publications
0
36
0
1
Order By: Relevance
“…Many times, the contribution of social workers in hospitals becomes unclear and remains unnoticed as it mixes with other disciplines that are also involved in the discharge planning process. According to Auerbach, Mason, and Laporte (2008), social workers in the acute care, settings deal with the most complex cases needing placement with multiple medical and social needs at discharge. The authors suggested that social workers are the paramount providers of patient assessment and are important coordinators of multiple patient needs at discharge.…”
Section: Social Work In Acute Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…Many times, the contribution of social workers in hospitals becomes unclear and remains unnoticed as it mixes with other disciplines that are also involved in the discharge planning process. According to Auerbach, Mason, and Laporte (2008), social workers in the acute care, settings deal with the most complex cases needing placement with multiple medical and social needs at discharge. The authors suggested that social workers are the paramount providers of patient assessment and are important coordinators of multiple patient needs at discharge.…”
Section: Social Work In Acute Health Carementioning
confidence: 99%
“…Furthermore, the authors suggested implementing tracking systems in hospitals to record empirical data in order to create accountability and gather feedback on social work practice in hospitals. Social work interventions in acute care settings are mostly related with multifaceted psychosocial needs of patients resulting in cost-effective health care delivery ( Auerbach & Mason, 2010;Auerbach, Mason, & Laporte, 2008). Cesta (2012) reiterated the importance of the social work practice in acute care settings, to be based on the best practices, while coordinating with other disciplines (Cesta, 2012).…”
Section: Social Work In Acute Health Carementioning
confidence: 99%
“…As Judd and Sheffield (20 1 0) point out, increased competition between nurses and social workers for scarce jobs continues to be a concern. Auerbach, Mason, and Laporte (2007) argue that nurses may be viewed by administrators as "more cooperative than social workers in facilitating speedy discharges" (p.…”
Section: Delineation Of Roles In Hospital Social Workmentioning
confidence: 99%
“…Services provided by social workers may be viewed as secondary activities in the hospital setting (Siefert, 1989), or nonessential when costs need to be cut (Auerbach et al , 2007). However, Egan and Kadushin (1995) found that social workers felt they were "better qualified than nurses to assess and intervene in social and emotional problems" (p. 3), while discharge planning is generally seen to be a social work responsibility.…”
Section: Delineation Of Roles In Hospital Social Workmentioning
confidence: 99%
See 1 more Smart Citation